Learning to Live Through Loss: Helping Children Understand Death: FCS2263/FY877, 11/2006 - Wilken, Carolyn S. (EDIS, 2006)
FCS-2263, a 5-page fact sheet by Carolyn Wilken, will assist parents and others as they help children understand and process the death of a loved one. Information covers both preschool children and older children. Includes a reading list. Published by the UF Department of Family, Youth and Community Sciences, November 2006.